SUMMARIES: STRUCTURE, TOPIC, MAIN POINTS - Jabborova Dildora Zokirjanovna; Abdulazizova Zarinabonu (TILSHUNOSLIK VA CHET TILLARNI O‘QITISHDA ZAMONAVIY RAQAMLI TEXNOLOGIYALARDAN FOYDALANISH MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This thesis examines extractive summarization systems and their operational principles. The topic focuses on how these systems generate concise, fluent summaries by identifying and concatenating salient sentences from single or multiple documents. The work is structured into three parts: core function and content selection, justification of extractive over abstractive methods, and three independent operational tasks. The main points include that extractive approaches are adaptable to users' information needs, function effectively for both single- and multi-document inputs, and involve three tasks: creating an intermediate representation, scoring sentences based on that representation, and selecting a summary consisting of several sentences. The introduction highlights critical design choices and explains how analyzing operational stages reveals advantages of certain techniques over others.